Pengaruh Inventory terhadap Profitabilitas PT. Indofood TBK Periode 2020-2023 - Catherine Yohanes; Elizabeth Tiur Manurung (Journal Of Business, Finance, and Economics (JBFE), 2025)
All companies are built and established with the aim of gaining profits which can later improve the company's image in front of the public. These profits are also expected to continue to increase consistently in each period. This study aims to determine the effect of inventory on the profitability of PT Indofood Tbk during the 2020-2023 period. This study uses data from the company's gacor777 annual financial report with a focus on inventory indicators such as Inventory Turnover Ratio (ITR) and profitability as measured by Return on Assets (ROA) and Net Profit Margin (NPM). The analysis method uses regression which aims to determine the relationship between the variables. The results of this study can show that the efficiency of inventory management does not have a significant impact on the company's profitability where optimal inventory turnover can contribute to increasing the company's profits. This study emphasizes several important things where the importance of an integrated inventory management strategy with other operational factors can increase the company's profits.